Integrating the Computer into a Business School Curriculum - MONTGOMERY, David B. (Institutional Knowledge at Singapore Management University, 1974)
The results of a study of computer utilization in the Graduate School of Business at Stanford are presented. The benefits and costs of a dedicated time-sharing system acquired by the Business School to supplement the central campus computer facility are discussed. The study showed that the time-sharing system produced many benefits, including improved service and a lower per student cost for computing. The implications of the Stanford experience for other schools are discussed.